"Legality with a Vengeance": Reclaiming Distribution for Sociolegal Studies. Issue 3 (3rd October 2018) - Levitsky, Sandra R.; Best, Rachel Kahn; Garrick, Jessica
Abstract : The law and society community has argued for decades for an expansive understanding of what counts as "law." But a content analysis of articles published in the Law & Society Review from its 1966 founding to the present finds that since the 1970s, the law and society community has focused its attention on laws in which the state regulates behavior, and largely ignored laws in which the state distributes resources, goods, and services. Why did socio‐legal scholars avoid studying how laws determine access to such things as health, wealth, housing, education, and food? We find that socio‐legal scholarship has always used "law on the books" as a starting point for analyses (often to identify departures in "law in action") without ever offering a programmatic vision for how law might ameliorate economic inequality. As a result, when social welfare laws on the books began disappearing, socio‐legal scholarship drifted away from studying law's role in creating, sustaining, and reinforcing economic inequality. We argue that socio‐legal scholarship offers a wide range of analytical tools that could make important contributions to our understanding of social welfare provision.